Fermionic Vacuum Stresses In Models With Toroidal Compact Dimensions - Saharian, A. A.; Avagyan, R. M.; Harutyunyan, G. H.; Nikoghosyan, G. H.
We investigate vacuum expectation value of the energy-momentum tensor for a massive Dirac field in flat spacetime with a toroidal subspace of a general dimension. Quasiperiodicity conditions with arbitrary phases are imposed on the field operator along compact dimensions. These phases are interpreted in terms of magnetic fluxes enclosed by compact dimensions. The equation of state in the uncompact subspace is of the cosmological constant type. It is shown that, in addition to the diagonal components, the vacuum energy-momentum tensor has nonzero off-diagonal components. In special cases of twisted (antiperiodic) and untwisted (periodic) fields the off diagonal components vanish. For untwisted fields the vacuum energy density is positive and the energy-momentum tensor obeys the strong energy condition. For general values of the phases in the periodicity conditions the energy density and stresses can be either positive or negative. The numerical results are given for a Kaluza-Klein type model with two extra dimensions.
Keywords: Astrophysics